2013
DOI: 10.1371/journal.pone.0059349
|View full text |Cite
|
Sign up to set email alerts
|

Association between Age at Diagnosis of Graves' Disease and Variants in Genes Involved in Immune Response

Abstract: BackgroundGraves' disease (GD) is a complex disease in which genetic predisposition is modified by environmental factors. The aim of the study was to examine the association between genetic variants in genes encoding proteins involved in immune response and the age at diagnosis of GD.Methods735 GD patients and 1216 healthy controls from Poland were included into the study. Eight genetic variants in the HLA-DRB1, TNF, CTLA4, CD40, NFKb, PTPN22, IL4 and IL10 genes were genotyped. Patients were stratified by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 44 publications
4
37
2
1
Order By: Relevance
“…Other Polish studies [29, 30, 31] focused mostly on CTLA-4 c.49A>G (rs231775) and revealed a significant association of this marker with disease; however, we did not. On the other hand, the association of the marker CT60 (rs3087243) observed in our group was not as significant as in another study of Polish patients with GD [29].…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…Other Polish studies [29, 30, 31] focused mostly on CTLA-4 c.49A>G (rs231775) and revealed a significant association of this marker with disease; however, we did not. On the other hand, the association of the marker CT60 (rs3087243) observed in our group was not as significant as in another study of Polish patients with GD [29].…”
Section: Discussioncontrasting
confidence: 88%
“…This finding may provide some evidence in support of our hypothesis; specifically that the superiority of the association defined as one susceptible locus expressed as the haplotype over the individual polymorphism association. As compared to other studies, which describe only univariate analyses [28, 29, 30, 31], our research takes a deeper and more detailed approach. The most GD-essential genetic marker in our study, CTLA-4 g.*642AT(8_33), was also relevant in other populations [2, 18, 25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some papers have confirmed an association between HLADRB1*03 and GO [48]–[49]. However, other authors have not found differences in the distribution of the HLADRB1*03 allele in GD patients with or without GO [10], [27], [50][51]. There is no sufficient evidence to support a correlation between the C(1858)T polymorphism in the PTPN22 gene and GO [29], [42].…”
Section: Discussionmentioning
confidence: 99%
“…Так, в ряде иссле дований показана ассоциация различных полимор физмов гена TNF α и БГ в различных популяциях [13,14,15,16,17]. В недавнем исследовании был вы явлен TNFb3 TNF 308 G гаплотип, имеющий самую сильную ассоциацию с БГ, по данным современного метаанализа [18].…”
Section: Discussionunclassified